The State of Exhaustion in the Work of Daniele Ciprì and Franco Maresco: An Exploration via the World, Bodies, and Gesture - Miralles, Joan Jordi (Quaderni d'Italianistica, 2025)
This essay explores the television and cinematographic work of Sicilian filmmakers Daniele Ciprì and Franco Maresco from a posthumanist perspective with a view to examine the state of exhaustion as the main common denominator within the settings, bodies and gestures of their films. As Rosi Braidotti points out, the state of exhaustion becomes a generative precondition to learn to think differently, and to put an affirmative ethics into practice (Braidotti, Posthuman Knowledge 18–19). Reviewing the work of the two Palermitani in a posthumanist key allows us to examine their cynical and dejected world from a new, positive and edifying perspective. Segments of Daniele Ciprì and Franco Maresco’s television program Cinico TV (1989–96) will be analysed, as well as their film Lo zio di Brooklyn (The Uncle from Brooklyn; 1995). My aim is to vindicate the work of two radical but still little-known filmmakers, who are essential to understanding the power of film and television in combating the homogeneity and aesthetic and narrative indoctrination of the media.